2016
DOI: 10.1051/0004-6361/201628165
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of oscillatoryα2dynamos in spherical wedges

Abstract: Context. Large-scale dynamo simulations are sometimes confined to spherical wedge geometries by imposing artificial boundary conditions at high latitudes. This may lead to spatio-temporal behaviours that are not representative of those in full spherical shells. Aims. We study the connection between spherical wedge and full spherical shell geometries using simple mean-field dynamos. Methods. We solve the equations for one-dimensional time-dependent α 2 and α 2 Ω mean-field dynamos with only latitudinal extent t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…We find that the dynamo properties are generally strongly influenced by the choice of boundary conditions. This can be particularly important when the magnetic field is strong near the boundary, as was seen recently in connection with the latitudinal boundary condition for simple α 2 mean-field dynamos (Cole et al 2016) in the wedge geometry that we consider here too. In all of our simulations a toroidal field tends to form preferentially near the surface of the convection zone but it is pushed down by a radial field boundary condition.…”
Section: Resultssupporting
confidence: 53%
“…We find that the dynamo properties are generally strongly influenced by the choice of boundary conditions. This can be particularly important when the magnetic field is strong near the boundary, as was seen recently in connection with the latitudinal boundary condition for simple α 2 mean-field dynamos (Cole et al 2016) in the wedge geometry that we consider here too. In all of our simulations a toroidal field tends to form preferentially near the surface of the convection zone but it is pushed down by a radial field boundary condition.…”
Section: Resultssupporting
confidence: 53%
“…Masada & Sano (2014) confirmed this finding for a dynamo in Cartesian geometry and reinforced the suggestion that the solar dynamo might indeed be of α 2 type. Then, Cole et al (2016) found that the oscillatory α 2 dynamo requires highly conducting plasma at high latitudes or, alternatively, a perfectly conducting boundary condition at high latitudes, as is often assumed in spherical wedge simulations (Mitra et al 2009). This was then confirmed through the realization that an oscillatory migratory α 2 dynamo is possible even with constant α effect provided there are two different boundary conditions on the two sides (Brandenburg 2017).…”
Section: Solar Equatorward Migration From An Oscillatory α 2 Dynamomentioning
confidence: 97%
“…Earlier mean-field simulations of αΩ dynamos have suggested that solutions with a perfect conductor boundary condition are similar to those in full spherical shells (Jennings et al 1990). However, more recent work by Cole et al (2016) has demonstrated that this conclusion is not generally valid and depends on the nature of the solutions. Their work also suggests that the use of a normal field boundary condition at high latitudes might be a better way of obtaining solutions that are applicable to full spherical shells.…”
Section: Introductionmentioning
confidence: 98%